Fenomen Matki Teresy z Kalkuty – uznanie misjonarki na arenie międzynarodowej - Wiktoria Noskiewicz (Studia Paradyskie)
The analysis of the phenomenon of Agnes Gonxha Bojaxhiu, known as Mother Teresa of Calcutta, and her global recognition focuses on the factors influencing her recognition on the international stage. Mother Teresa's authority developed through numerous meetings with world leaders and prestigious awards, including the Nobel Peace Prize. The basis of the article is a chapter from the bachelor's thesis, "Global Public Opinion on the Activities of Mother Teresa of Calcutta," which allows for a deeper understanding of the impact of her charitable actions on a global scale. The evaluation of these events relates to shaping public opinion about Mother Teresa. One of the main conclusions emphasizes the global significance of Mother Teresa's actions and her influence on the international community. The missionary is not only a symbol of benevolence but also an inspiration to many people worldwide. Her work has become a stimulus for social initiatives, inspiring action for the benefit of others and the environment. This legacy shapes our perception of altruism and social engagement. An analysis of the life aspects of Mother Teresa prompts reflection on the universal values that guided her and their significance in today's world. This article allows for an evaluation of her legacy and accomplishments worldwide. A figure originating from the Catholic Church can be subject to reflection regarding the significant changes she brought about on the international stage and how she was perceived.